The phase and magnitude of hair cell receptor potentials and frequency tuning in the guinea pig cochlea - Kossl, M (J Neurosci, 1992)
Voltage responses to tones were recorded intracellularly from inner (IHC) and outer (OHC) hair cells in the basal turn of the guinea pig cochlea. Tone-evoked voltage responses were also recorded extracellularly from fluid-filled spaces adjacent to the hair cells and from supporting cells. The AC component of the OHC voltage responses to tones at frequencies between 8 and 24 kHz and those recorded extracellularly were remarkably similar with respect to phase as a function of sound level, but the magnitude of the AC response was 2–10 times larger when recorded intracellularly from an OHC. At frequencies more than half an octave below the characteristic frequency (CF), the phase of OHC AC response was independent of level, and the slope of the magnitude/level functions was 1 dB/db. At levels exceeding about 70 dB SPL, the slopes became less steep and depolarizing IHC and OHC DC responses appeared. At frequencies one-half an octave below CF and at frequencies between one-third and one-half an octave above CF, notches were present in the AC/level function between 70–100 dB SPL that were accompanied by a sudden phase lag of -180 degrees. These frequency- and level-dependent characteristics were also present in relatively insensitive preparations and were attributed to a change in the phase of OHC excitation due to level-dependent changes in the relative stiffness of the mechanical components of the cochlear partition. At CF the detection thresholds of the OHC AC response and IHC DC response and slopes of the response/level functions were similar. At sound levels around 60 dB SPL, the AC signal began to phase lead, amounting to approximately 90 degrees at 70 dB SPL. Within the same range of levels, the OHC DC potentials first appeared and the IHC DC response began to saturate. At frequencies just above the CF, the phase of the AC component increased with level to a lead of about 180 degrees. OHC and IHC tuning curves are comparable in the tip region, but they differ in that the low- and high-frequency shoulders of the OHC AC tuning curves are more sensitive by 10–30 dB SPL. On the basis of the frequency- and level-dependent characteristics of the IHC and OHC responses, it is proposed that OHC AC potentials provide a measure of the phase and magnitude of the proposed electromechanical feedback of the cochlear partition that enhance frequency tuning in the cochlea.